SHIFTING FROM DISCLOSURE TO ACTION: EMPOWERING STAKEHOLDERS VIA SUSTAINABILITY REPORTING - Dwi Wulandari; Rahmawati Rahmawati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to determine the transition from openness to action in empowering stakeholders through reporting permits. The object of this research is companies registered in the Asia Sustainability Reporting Rating (ASRRAT) 2018-2022. The method used in this research is quantitative using the Eviews 12 program. This study uses purposive sampling method and obtained 60 companies in the Asia Sustainability Reporting Rating for five years. The research results show that managerial ownership influence the spread of sustainability reporting, while profitability, liquidity and audit committees do not influence the disclosure of sustainability reporting with variabel control leverage and company size.